A model for prediction of nearby population and in-plant workers exposure to air pollutants released from industrial facilities - Chong, Gracie Shih Chin (Universiti Malaysia Sarawak, UNIMAS, 2004)
This dissertation is about the design of the system for the proposed BDC Housing Development Scheme at Block 8 Klauh Land District, Sri Aman Division. The design is based on Malaysia Jabatan Kerja Raya (JKR) Standard which was adapter to MWA Design Guidelines for Water Supply Systems. The size and type of pipes were determined to meet the requirement of the Standard. The WaterCAD software that developed by Haestad Method Inc. was used to perform the analysis of the system. Several demand scenarios were analyzed for the system such as a average daily, demand peak hour demand and critical demand at junction.